Effect of norepinephrine infusion on hepatic blood flow and its interaction with somatostatin: an observational cohort study - Jurgen van Limmen; Xavier Iturriagagoitia; Marilie Verougstraete; Piet Wyffels; Frederik Berrevoet; Luís Filipe Abreu de Carvalho; Stefan De Hert; Luc De Baerdemaeker (BMC Anesthesiology, 2022)
Abstract Background Norepinephrine (NE) is a α1-adrenergic mediated vasopressor and a key player in the treatment of perioperative hypotension. Apart from modulating systemic hemodynamics, NE may also affect regional blood flow, such as the hepatic circulation, which contains a wide variety of adrenergic receptors. It may alter regional vascular tonus and hepatic blood flow (HBF) by reducing portal vein flow (PVF) or hepatic arterial flow (HAF). The aim of this study was to assess the effects of NE on HBF. Methods Patients scheduled for pancreaticoduodenectomy were included. All patients received standardized anesthetic care using propofol and remifentanil and were hemodynamically stabilized using a goal-directed hemodynamic strategy guided by Pulsioflex™. On surgical indication, somatostatin (SOMATO) was given to reduce pancreatic secretion. HBF measurements were performed using transit-time ultrasound (Medistim™). Baseline hemodynamic and HBF measurements were made after pancreatectomy, at T1. Afterwards, NE infusion was initiated to increase mean arterial pressure (MAP) by 10 – 20% of baseline MAP (T2) and by 20 – 30% of baseline MAP (T3). HBF and hemodynamic measurements were performed simultaneously at these three time-points. Results A total of 28 patients were analyzed. Administration of NE significantly increased MAP but had no effect on cardiac index. NE infusion reduced total HBF in all patients (p < 0.01) by a reduction HAF (p < 0.01), while the effect on PVF remained unclear. Post-hoc analysis showed that SOMATO-treated patients had a significant lower PVF at baseline (p < 0.05), which did not change during NE infusion. In these patients, reduction of total HBF was primarily related to a reduction of HAF (p < 0.01). In untreated patients, NE infusion reduced total HBF both by a reduction HAF (p < 0.01) and PVF (p < 0.05). Conclusion Administration of NE reduced total HBF, by decreasing HAF, while the effect on PVF remained unclear. SOMATO-treated patients had a lower PVF at baseline, which remained unaffected during NE infusion. In these patients the decrease in total HBF with NE was entirely related to the decrease in HAF. In SOMATO-untreated patients PVF also significantly decreased with NE. Trial registration Study protocol EC: 2019/0395. EudraCT n°: 2018–004,139-66 (25 – 03 – 2019). Clin.trail.gov: NCT03965117 (28 – 05 – 2019).